2012
DOI: 10.1117/12.923859
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with water-soluble phtalocyanines against bacterial biofilms in teeth root canals

Abstract: The study presents the PDT with metal phthalocyanines on biofilms grown in root canals of ten representatives of the Gram-positive and the Gram-negative bacterial species and a fungus Candida albicans which cause aqute teeth infections in root canals.. The extracted human single-root teeth infected for 48 h with microorganisms in conditions to form biofilms of the above pathogens were PDT treated. The stage of biofilm formation and PDT effect of the samples of the teeth were determined by the scaning electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…[24][25][26] The results in the third group with Fotosan (III.1) demonstrated a more effective antibacterial action against Gram positives (4.5-7 log 10 ), and a less powerful effect (approximately 100-1000 times) against the variety of Gram-negative rods and C. albicans: 2.5-4.6 log 10 (P < 0.001, Table 2, Figure 2). The PDT with Fotosan used in the present study, and the PDT using complexes of zinc with phthalocyanine (ZnPc and ZnPcMe) and complexes of silicon with phthalocyanine (SiPc) as photodynamic agents used in our previous study, 5 showed similar active bactericidal and fungicidal actions. The use of PDT with Fotosan in the present study and ZnPcMe in the previous one gave more satisfying results than the use of lasers alone (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…[24][25][26] The results in the third group with Fotosan (III.1) demonstrated a more effective antibacterial action against Gram positives (4.5-7 log 10 ), and a less powerful effect (approximately 100-1000 times) against the variety of Gram-negative rods and C. albicans: 2.5-4.6 log 10 (P < 0.001, Table 2, Figure 2). The PDT with Fotosan used in the present study, and the PDT using complexes of zinc with phthalocyanine (ZnPc and ZnPcMe) and complexes of silicon with phthalocyanine (SiPc) as photodynamic agents used in our previous study, 5 showed similar active bactericidal and fungicidal actions. The use of PDT with Fotosan in the present study and ZnPcMe in the previous one gave more satisfying results than the use of lasers alone (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 66%
“…Problematic Gram‐negative bacteria, such as K. pneumoniae and P. aeruginosa , form very thick biofilms in root canals. Some achieve that through the overproduction of exopolysaccharide alginate . Most Gram‐negative clinical isolates are MDR, and their outer membrane endotoxin (lipopolysaccharide) and their ability to produce toxic nitrogen metabolites additionally contribute to the pathogenesis of endodontic inflammations …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations